Methodological guidelines and publications of benefit–risk assessment for health technology assessment: a scoping review protocol - Patricia Coelho De Soárez; Uwe Siebert; Franciele Cordeiro Gabriel; Beate Jahn; Bruna De Oliveira Ascef; Erica Aranha Suzumura; Fernando Henrique de Albuquerque Maia; Aline Frossard Ribeiro Bortoluzzi; Natalia Santos Farias (BMJ Open)
Background Benefit–risk assessment (BRA) is used in multiple phases along the health technology’s life-cycle to evaluate the balance between the benefits and risks, as it is fundamental to all stakeholders. BRA and its methodological approaches have been applied primarily in the context of regulatory agencies. However, BRA’s application and extent in the context of health technology assessment (HTA) bodies remain less clear. Our goal is to perform a scoping review to identify and map methodological guidelines and publications on methods of BRA. This will be done considering the different phases of the life-cycle of health technologies to underline both the depth and extent of research concerning BRA, especially in the context of HTA.Methods and analysis This scoping review protocol was developed following the framework proposed by Arksey and O’Malley, and the updated guidelines by the Joanna Briggs Institute. We will include methodological publications that provide recommendations or guidelines on methods for BRA. We will conduct electronic searches on Medline (PubMed) and EMBASE (Ovid) databases; manual searches on the main websites of HTA bodies and drug regulatory organisations; and contact experts in the field. Systematic extraction forms will be used to screen and assess the identified publications by independent assessors. We will provide a qualitative synthesis using descriptive statistics and visual tools. Results will be summarised in systematic evidence tables and comparative evidence scoping charts.Ethics and dissemination This review will use data publicly available and does not require ethics approval. The results of this scoping review will contribute to scientific knowledge and act as a basis for methodologists, guideline developers and researchers for the development of BRA to inform regulatory decisions, reimbursement and coverage decision making. The results will be disseminated through peer-reviewed articles, conferences, policy briefs and workshops.Trial registration number Open Science Framework (https://doi.org/10.17605/OSF.IO/69T3V).